A study on wear assessment of AA6061-B4C-Nanographite hybrid composite. (2020) - Rajkumar, K.; Ramraji, K.; Nambiraj, K.M.; Gnanavelbabu, A.
Abstract: Wear performance of aluminium metal matrix composites have reached essential research studies for the application of tribo components or products. This research paper aims to fabricate the aluminum alloy composite with various combinations of Nano Graphite (NG) and boron carbide particles and select a relatively superior wear resistance composite in relation to the wear rate and surface characteristics. A two-step stir casting method was adopted for the production of AA6061-B4 C-nanographite hybrid composites. Wear performance of fabricated composites were tested in a pin-on-disc tribometer with consideration of constant parameter of sliding distance, speed, and normal load. Experiment results showed that a combination of 10 vol% of nanographite and boron carbide particles exhibited a superior wear performance due to the synergetic effect of both particles existed at the contact zone. These developed materials will be used in brake pad, automotive brake rotor, and sliding member of light machine tools.